Pemanfaatan Limbah Plastik Berjenis HDPE Dan PET Sebagai Subtitusi Agregat Terhadap Sifat Mekanik Paving Block: Pemanfaatan Limbah Plastik Berjenis HDPE Dan PET Sebagai Subtitusi Agregat Terhadap Sifat Mekanik Paving Block - Siti Annisa Samosir; Nursyamsi Nursyamsi; Johannes Tarigan (Universitas Muhammadiyah Sidoarjo, 2025)
The utilization of waste as a substitute material for aggregate in paving blocks has become an effective and innovative option. One of the largest contributors to global plastic waste is Polyethylene Terephthalate (PET) bottles and High Density Polyethylene (HDPE) bottle caps, both of which are types of plastic that can be used in paving mixtures due to their strength and easy availability. This research aims to examine the effects of using plastic bottle waste and bottle cap waste as aggregate substitutes on the mechanical properties of paving blocks, including impact testing and cost analysis. The results of this study show that PET variations perform better than HDPE. A 5% PET plastic variation produced the highest compressive strength of 22.32 MPa, while the lowest compressive strength was recorded with a 15% HDPE variation at 14.62 MPa. In addition to mechanical performance, paving blocks with PET variations are capable of reducing up to 2.45 kg of plastic bottles per 1 m².The utilization of waste as a substitute material for aggregate in paving blocks has become an effective and innovative option. One of the largest contributors to global plastic waste is Polyethylene Terephthalate (PET) bottles and High Density Polyethylene (HDPE) bottle caps, both of which are types of plastic that can be used in paving mixtures due to their strength and easy availability. This research aims to examine the effects of using plastic bottle waste and bottle cap waste as aggregate substitutes on the mechanical properties of paving blocks, including impact testing and cost analysis. The results of this study show that PET variations perform better than HDPE. A 5% PET plastic variation produced the highest compressive strength of 22.32 MPa, while the lowest compressive strength was recorded with a 15% HDPE variation at 14.62 MPa. In addition to mechanical performance, paving blocks with PET variations are capable of reducing up to 2.45 kg of plastic bottles per 1 m².Highlight : Paving blocks with 5% PET or HDPE meet strength standards for parking use while reducing water absorption. Higher plastic content (>5%) weakens mechanical and impact resistance due to poor bonding. Using PET 5% cuts material costs and reduces plastic waste by 245 kg per 100 m² area. Keywords : Paving Block, Plastic Waste, HDPE, PET, Mechanical Strength